Altitude training and endurance performance - Wilbur, R. (1998)
Dr. Wilbur presented an overview of the literature on altitude training. He covered the areas of scientific evidence and anecdotal evidence of altitude training. He discussed the limitations in altitude training in relation to training intensity, the biochemical response and the cardio pulmonary response. He also covered the alternative models in altitude training including the high/low approach, the nitrogen houses and supplemental oxygen. He referred back to the Mexico City Olympic Games where World Records were set in 100m, 200m & 400m events including hurdle events and field events (e.g. long jump). No world records were set in events more than 800 metres although the 800 metre world record was equalled in the Men's. He discussed the most well known studies done on altitude training, studies using no control group and studies using a control group. The best known study is that of Daniels & Alderidge who were the first to studied the high/low model on elite athletes. Five of their six subjects set World or personal records during the period of the study! This study is considered the grand daddy of high/low altitude training studies.